Transposição didática em literatura clássica em história em quadrinhos: letramento e formação de leitores nas séries iniciais do ensino fundamental - Dias, Artenizia Leonel (Universidade Federal do Tocantins, 2023)
The present study is linked to the research line Methods and Techniques of Teaching and Learning in Basic Education of the Professional Graduate Program in Education - PPPGE of the Federal University of Tocantins and seeks to contribute to the theoretical and practical debate about the challenges in the didactic transposition in children's literacy, i.e., the transformation of historical and culturally accumulated knowledge into school knowledge, in the context and level of cognitive and psychosocial development of the student. In this perspective, we raise the following question: how does the process of literacy, literacy and formation of readers occur from the perspective of the didactic transposition of classical literature into comic books for students of the 1st year of elementary school? To answer it, we have as the main objective of the research to understand the process of literacy and formation of readers in the perspective of the didactic transposition of classical literature into comic books for students in the 1st year of elementary school. Our specific objectives were To apprehend the theoretical contributions about the literacy process, and formation of readers in the initial grades of elementary school; To identify how reading practices in classical literature in the classroom can contribute to the formation of readers in initial grades; To know how the didactic transposition of classic literature into comics facilitates the learning of reading and writing processes; To describe didactic-pedagogical reading practices in classic literature in the form of comic books that awaken in children the taste for reading and to analyze how the student makes conscious use of language practices, based on classic literature in the format of comic books. As methodological procedures, we adopted the qualitative approach, of the research-action type, having as participants the teacher-researcher and the children of a first year class of Elementary School of a municipal full-time school located in Palmas, Tocantins, the children participating in the research (26 students) were chosen for being students who started their literacy process. In the form of data analysis, we used the interpretative research, because this allowed us to use several theoretical matrices in the analysis data generated in the study. The data were analyzed based on two categories of analysis: Social and cultural aspects via literary literacy: in the work "O Quinze" (The Fifteen) by Rachel de Queiroz and The human virtues and moral renovations in literary literacy: in the work "Os Miseráveis" (The Miserable’s) by Victor Hugo. As research instruments we used structured and semi-structured interviews, as well as oral reports narrated by the students during the classes, and reading of the selected works in comic books format. Among some results found, the activities related to the classic works "O Quinze" and "Os Miseráveis" allowed us to understand that the choice of the works in comic books format was fundamental for the themes to be developed and for the children to show more interest in reading the works and, consequently, to understand cultural and social aspects present in these stories, via didactic transposition. In the study, it was also evidenced that educational practices when integrated to the reality of the child, being reflective and meaningful, guarantee the expansion of the levels of school literacy, collective, and individual literacy.